Introduction to school counseling - Wright, Robert J. (SAGE Publications, 2012)
A solid grounding in measurement and research helps readers develop the ability to interpret, evaluate, and explain standardized test scores and other data to colleagues, students, and parents. It also empowers the school counselor to take a leadership role in school-based action research and program evaluation. --